Social isolation affects intra‐specific interaction behaviour and reduces the size of the cerebellar brain region in juvenile Atlantic salmon Salmo salar. Issue 3 (13th July 2022) - Guo, Haoyu; Näslund, Joacim; Thomassen, Søren T.; Larsen, Martin H.
Abstract: The social environment can affect the development of behavioural phenotypes in fish, and it is important to understand such effects when rearing fish in artificial environments. Here, the authors test the effects of spatial isolation on social interaction propensity and brain development in hatchery‐reared Atlantic salmon Salmo salar L. Salmon reared in isolation generally stayed further away from a conspecific in a standardized intruder test than conspecifics reared together in groups. Isolated salmon also tended to be more active in an intruder test, albeit non‐significantly so, but this pattern was not detected in open‐field tests without an intruding conspecific. The cerebellar brain region was relatively smaller in isolated salmon, suggesting that the brain was developing differently in these fish. Therefore, some features of the behavioural and neural phenotype are affected by rearing in isolation. These effects should be considered when rearing salmon, particularly for experimental purposes as it may affect results of laboratory studies on behavioural expression and brain size.